Solitary Fibrous Tumor of Neck Mimicking Cold Thyroid Nodule in 99m Tc Thyroid Scintigraphy. (1st October 2013) - Topaloglu, Oya; Ucan, Bekir; Demirci, Taner; Sayki Arslan, Muyesser; Saylam, Guleser; Onder, Evrim; Gultekin, Sinan; Dilli, Alper; Sahin, Mustafa; Cakal, Erman; Ozbek, Mustafa; Delibasi, Tuncay
Abstract : A 68-year-old man had a rapidly growing, painless neck mass, thought to be nodular goiter. Ultrasonography showed a giant, heterogeneous mass occupying the middle and superior poles and protruding outside of the left thyroid lobe. The results of the thyroid function tests were normal. Thyroid scintigraphy revealed a large hypoactive nodule in the left thyroid lobe. Complete surgical removal of tumor was performed and macroscopically demonstrated a well-demarked lesion outside the thyroid gland. Microscopically, the lesion was composed of fibroblast-like spindle cells in a patternless architecture and extensive stromal hyalinization. Immunohistochemistry showed positive reaction for CD34 in spindle cells and diffuse bcl-2 staining. The pathology was confirmed as solitary fibrous tumor. In the follow-up period after surgery, thyroid scintigraphy showed normal left thyroid lobe. Solitary fibrous tumor originated from or associated with thyroid gland is extremely rare. According to our knowledge, this is the first reported solitary fibrous tumor presenting like a cold thyroid nodule. This pathology must be considered for differential diagnosis of neck masses in the thyroid region.